Mykola Mahera’s Fairy-Tales – as a Mean of Primary Schoolchildren Moral Upbringing - Galuna Tkachuk (Pedagogical Discourse, 2012)
The problem of moral upbringing of primary schoolchildren with the help of the content of the fairy-tales of Mykola Mahera, Podillia region children’s writer, has been raised in the article